Mental health, mother-child interaction and development at the end of the first year of life - Ribeiro, Débora Gerardo [UNESP]; Perosa, Gimol Benzaquen [UNESP]; Padovani, Flávia Helena Pereira [UNESP] (FapUNIFESP (SciELO), 2014)
Abstract: Maternal mental health can affect the quality of the mother-child interaction and, consequently, the development of the child. This study aimed to evaluate the relationship between the mother-child interaction and the neuro-psychomotor development of children at one year of age, taking into consideration the maternal mental health. A total of 65 children, who were registered in Family Health Units, participated, along with their mothers, who responded to a screening interview for common mental disorders. Development was evaluated through a risk screening test. The interaction was assessed through the Dyadic Interaction Assessment Protocol. Developmental risk was presented by 43.1% of the children. Although 44.6% of the mothers presented scores indicative of psychological distress, maternal mental health was not associated with the interactive behaviors. Some maternal and child behaviors were associated with developmental delays, however, only cognitive stimulation was shown to be a predictor of delays. The data contribute to the comprehension of the role of the interaction in child development.

Resumen: La salud mental materna puede afectar la calidad de la interacción madre-hijo y el desarrollo infantil. Este estudio evaluó la relación entre interacción madre-hijo y el desarrollo neuropsicomotor de niños con edad de un año, considerando la salud mental materna. Fueron evaluados 65 niños de un año, usuarios de Unidades de Salud de la Familia, mediante una prueba de detección del riesgo. Las madres fueron entrevistadas y respondieron a instrumento de rastreo psiquiátrico. Se evaluó la interacción mediante un protocolo de interacción diádica. 43,1% de los niños presentó riesgo de desarrollo. Aunque 44,6% de las madres presentó malestar psicológico, su salud mental no se asoció con los comportamientos presentados en la interacción. Sin embargo, comportamientos interactivos de la madre y del niño se asociaron con retraso en el desarrollo. La estimulación cognitiva fue la única variable predictiva de retrasos. Los datos contribuyen para la comprensión del papel de la interacción y el desarrollo infantil.

Resumo: A saúde mental materna pode afetar a qualidade da interação mãe-criança e, consequentemente, o desenvolvimento infantil. Este estudo teve como objetivo avaliar a relação entre interação mãe-filho e o desenvolvimento neuropsicomotor de crianças com um ano de vida, levando em consideração a saúde mental materna. Participaram 65 crianças, usuárias de Unidades de Saúde da Família, e suas mães que responderam a uma entrevista de rastreio para transtorno mental comum. Avaliou-se o desenvolvimento por meio de um teste para rastreamento de risco. A interação foi avaliada pelo Protocolo de Avaliação de Interação Diádica. Apresentaram risco desenvolvimental 43,1% das crianças. Apesar de 44,6% das mães pontuarem para sofrimento psíquico, a saúde mental materna não se associou aos comportamentos interativos. Alguns comportamentos maternos e infantis associaram-se a atrasos desenvolvimentais, mas apenas a estimulação cognitiva mostrou-se preditora de atrasos. Os dados contribuem para compreensão do papel da interação no desenvolvimento infantil.
Salud mental, interacción madre-hijo y desarrollo al final del primer año de vida
Saúde mental, interação mãe-criança e desenvolvimento ao final do primeiro ano de vida
Keywords: Child development; Mother-child relationships; Risk factors; Mental health; Desarrollo infantil; Relaciones madre-niño; Factores de riesgo; Salud mental; Desenvolvimento infantil; Relações mãe-criança; Fatores de risco; Saúde mental